In Vitro Oocyte Culture-Based Manipulation of Zebrafish Maternal Genes - Nair, Sreelaja (2012)
In animals, females deposit gene products into developing oocytes, which drive early cellular events in embryos immediately after fertilization. As maternal gene products are present before fertilization, the functional manipulation of maternal genes is often challenging to implement, requiring gene expression or targeting during oogenesis. Maternal expression can be achieved through transgenesis, but transgenic approaches are time consuming and subject to undesired epigenetic effects. Here, we have implemented in vitro culturing of experimentally manipulated immature oocytes to study maternal gene contribution to early embryonic development in the zebrafish. We demonstrate phenotypic rescue of a maternal-effect mutation by expressing wild-type product in cultured oocytes. We also generate loss-of-function phenotypes in embryos through either the expression of a dominant-negative transcript or injection of translation-blocking morpholino oligonucleotides. Finally, we demonstrate subcellular localization during the early cell divisions immediately after fertilization of an exogenously provided maternal product fused to a fluorescent protein. These manipulations extend the potential to carry out genetic and imaging studies of zebrafish maternal genes during the egg-to-embryo transition.